2014
DOI: 10.1016/j.metabol.2014.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Lactation intensity and fasting plasma lipids, lipoproteins, non-esterified free fatty acids, leptin and adiponectin in postpartum women with recent gestational diabetes mellitus: The SWIFT cohort

Abstract: Objectives Lactation may influence future progression to type 2 diabetes after gestational diabetes mellitus (GDM). However, biomarkers associated with progression to glucose intolerance have not been examined in relation to lactation intensity among postpartum women with previous GDM. This study investigates whether higher lactation intensity is related to more favorable blood lipids, lipoproteins and adipokines after GDM pregnancy independent of obesity, socio-demographics and insulin resistance. Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 45 publications
5
37
0
2
Order By: Relevance
“…In women who continue breastfeeding for 1 year, higher levels of HDL appear to persist until weaning 15 . In the Kaiser SWIFT cohort, greater breastfeeding intensity was associated with higher HDL and lower LDL 16 at 6 to 9 weeks postpartum.…”
Section: Lactation and Short-term Markers Of Metabolic Healthmentioning
confidence: 96%
“…In women who continue breastfeeding for 1 year, higher levels of HDL appear to persist until weaning 15 . In the Kaiser SWIFT cohort, greater breastfeeding intensity was associated with higher HDL and lower LDL 16 at 6 to 9 weeks postpartum.…”
Section: Lactation and Short-term Markers Of Metabolic Healthmentioning
confidence: 96%
“…In postpartum women with recent GDM, lactation enhances β-cell compensation for insulin resistance, resulting in better insulin sensitivity, glucose effectiveness, and first-phase insulin response to glucose according to the Bergman Minimal Model (9). In SWIFT, we previously reported an inverse association for lactation intensity and fasting blood lipids, glucose, and insulin resistance as well as the prevalence of prediabetes at study baseline independent of body mass index, race, or other risk factors (5, 6). …”
Section: Discussionmentioning
confidence: 94%
“…Characteristics of included studies are shown in Table 1. All the included women had a history of GDM, while the diagnostic criteria were various, involving the International Association of Diabetes and Pregnancy Study Group criteria, 20,21,27,31 the American Diabetes Association criteria, 28,41 the World Health Organization criteria, 25 Carpenter-Coustan criteria, 26,[29][30][31]33,37 the National Diabetes Data Group criteria, 43,45 and some local criteria. 24,35,44,46 Two kinds of BF measure (status, intensity) were used to describe and group the exposure in each study, with different distinction points, ranged from BF initiation to 12 months.…”
Section: Characteristics and Quality Of Included Studiesmentioning
confidence: 99%
“…Quality assessments using RoBANS are summarized in Table S2. A total of 12 studies 23,26,27,[30][31][32]34,35,37,[43][44][45] with diabetes-free at baseline had a low risk of selection bias caused by selection of participants. Meanwhile, seven studies 20,[23][24][25]35,40,43 had a low risk of confounding bias caused by confounding variables, due to the adequate adjustment for covariates.…”
Section: Characteristics and Quality Of Included Studiesmentioning
confidence: 99%